1999
DOI: 10.2176/nmc.39.748
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Primitive Trigeminal Artery Imaged by Three-dimensional Computed Tomography Angiography —Two Case Reports—

Abstract: Three-dimensional computed tomography (3D CT) angiography was used to investigate two cases of persistent primitive arteries. 3D CT angiography and 3D CT demonstrated a persistent primitive trigeminal artery variant penetrating the lateral edge of the posterior clinoid process and running to the posterior medial side, and a persistent primitive trigeminal artery perforating the canal of the posterior clinoid process and the petrosal bone junction. 3D CT angiography can delineate these persistent primitive arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…DisCussion during the intracranial vascular development in the embryo (approximately 35 days of gestational age), four main temporally anastomosis arise between carotid and vertebral-basilar systems: the trigeminal, optical, hypoglossal and proatlantal intersegmental [1][2][3][4] . These anastomosis persist for about 1 week and disappear with the subsequent development of posterior communicants and vertebral arteries 1 .…”
Section: Cases 3 and 4 (Intra-selar Course)mentioning
confidence: 99%
See 4 more Smart Citations
“…DisCussion during the intracranial vascular development in the embryo (approximately 35 days of gestational age), four main temporally anastomosis arise between carotid and vertebral-basilar systems: the trigeminal, optical, hypoglossal and proatlantal intersegmental [1][2][3][4] . These anastomosis persist for about 1 week and disappear with the subsequent development of posterior communicants and vertebral arteries 1 .…”
Section: Cases 3 and 4 (Intra-selar Course)mentioning
confidence: 99%
“…The prevalence of a PTA in patients with trigeminal neuralgia is 2.2%, in a study performed by Bondt et al and neurovascular compression was assumed to be present if the patient showed clinical features of trigeminal neuralgia, if there was contact between an artery and the trigeminal nerve on the affected side, and if other pathology had been excluded 8 . The PTA is easily identified by MR angiography, however, the exact location of the drilling of the skull base is impossible to be identified by these methods 3 . small trigeminal arteries cannot be identified in spin-echo T1 and T2 sequences, it is only possible with the MR angiography 6 .…”
Section: Cases 3 and 4 (Intra-selar Course)mentioning
confidence: 99%
See 3 more Smart Citations